Effect of Fe Concentration on Fe-Doped Anatase TiO2 from GGA + U Calculations - Hsuan-Chung Wu; Sheng-Hong Li; Syuan-Wei Lin (International Journal of Photoenergy)
To comprehend the photocatalytic mechanisms of anatase Ti1−𝑥Fe𝑥O2 with various concentrations of Fe, this study performed first principles calculations based on density functional theory with Hubbard U on-site correction to evaluate the crystal structure, impurity formation energy, and electronic structure. We adopted the effective Hubbard U values of 8.47 eV for Ti 3d and 6.4 eV for Fe 3d. The calculations show that higher concentrations of Fe are easily formed in anatase TiO2 due to a reduction in the formation energy. The band gap of Fe-doped TiO2 decreases Fe doping level increases as a result of the overlap among the Fe 3d, Ti 3d, and O 2p states, which enhances photocatalytic activity in the visible light region. Additionally, a broadening of the valence band and Fe impurity states within the band gap might also contribute to the photocatalytic activity.